Sampling the structure and chemical order in assemblies of ferromagnetic nanoparticles by nuclear magnetic resonance - Yuefeng Liu (Nature Portfolio, 2016)
As nanoparticles possess technological applications from catalysis to medical therapies, methods to probe their structural properties are crucial. Here, the authors extend a nuclear magnetic resonance method to extract such properties for specific size ranges of noninteracting magnetic particles.